Characterization of Ganyong (Canna discolor) and Cowpea (Vigna unguiculata) Flour Affected by Heat Moisture Treatment - Yovani, Tania; Wangrimen, Gervasius Harwin; Fitriani, Aprilia (Journal of Agri-Food Science and Technology, 2022)
Cookies are food products that are often a consumption. High glycemic index (GI) cookies consumption causes increased diabetes mellitus (DM) cases. In addition, high GI cookies can improve obesity. DM and obesity lead to other complications and degenerative diseases. The low GI value cookies need to produce for diabetes mellitus prevention. This research is a preliminary study to produce raw material flour for low GI cookies. Heat moisture treatment (HMT) was applied to modify the Canna flour. Canna flour increased the moisture content to 34.39% wet base (w.b.), then dried at 92°C for 20.6 h. HMT process increased the resistance starch, soluble and insoluble fiber. Treated Ganyong flour has 2.16 % dry base (d.b.) soluble fiber, 30.19 % d.b., and 28.03% d.b. The result showed that HMT increased total dietary and soluble fiber. Those parameters are essential to low GI cookies for diabetes mellitus prevention. HMT also increased the whiteness index of Ganyong flour.